2012
DOI: 10.1155/2012/246725
|View full text |Cite
|
Sign up to set email alerts
|

Self-Referential Thinking, Suicide, and Function of the Cortical Midline Structures and Striatum in Mood Disorders: Possible Implications for Treatment Studies of Mindfulness-Based Interventions for Bipolar Depression

Abstract: Bipolar depression is often refractory to treatment and is frequently associated with anxiety symptoms and elevated suicide risk. There is a great need for adjunctive psychotherapeutic interventions. Treatments with effectiveness for depressive and anxiety symptoms as well as suicide-related thoughts and behaviors would be particularly beneficial. Mindfulness-based interventions hold promise, and studies of these approaches for bipolar disorder are warranted. The aim of this paper is to provide a conceptual ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 243 publications
(254 reference statements)
2
11
0
Order By: Relevance
“…We observed that the appearance of anhedonia at 7 days was selectively associated with an increased density of both D 1 and D 2 receptors in the striatum, together with a decreased short-term plasticity and increased dopaminergic sensitivity in corticostriatal synapses. This is in notable agreement with the involvement in operant motivation of aberrant dopaminergic signaling in the striatum [43][44][45][46], suggesting that abnormal dopaminergic control of striatal function might be selectively associated with the hedonic alterations observed 7 days after 6-OHDA administration. This is re-enforced by the observation that there was a parallel disappearance of anhedonic behavior as well as striatal dopaminergic alterations at 21 days after 6-OHDA administration.…”
Section: Discussionsupporting
confidence: 83%
“…We observed that the appearance of anhedonia at 7 days was selectively associated with an increased density of both D 1 and D 2 receptors in the striatum, together with a decreased short-term plasticity and increased dopaminergic sensitivity in corticostriatal synapses. This is in notable agreement with the involvement in operant motivation of aberrant dopaminergic signaling in the striatum [43][44][45][46], suggesting that abnormal dopaminergic control of striatal function might be selectively associated with the hedonic alterations observed 7 days after 6-OHDA administration. This is re-enforced by the observation that there was a parallel disappearance of anhedonic behavior as well as striatal dopaminergic alterations at 21 days after 6-OHDA administration.…”
Section: Discussionsupporting
confidence: 83%
“…Less is known about the role of the rostral prefrontal cortex in suicidal behavior. The experience of mental pain in attempters during recall of suicidal episodes showed associations with decreased functioning of the rostral prefrontal cortex (41), a region implicated in self-referential and introspective mental functions (42) altered in suicidal ideation and during suicidal acts (43). Frontal dysfunction was observed in a study of adult ideators (9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, potentially relevant studies were also identified from the reference lists of the included studies, reviews, and meta-analyses of interventions that used MBIs as adjunctive therapy to treat patients with BD (Chiesa and Serretti, 2011;Marchand, 2012;Mehrmann and Karmacharya, 2013;Sipe and Eisendrath, 2012).…”
Section: Eligibility Criteriamentioning
confidence: 99%